HO-1 mediates the anti-inflammatory actions of Sulforaphane in monocytes stimulated with a mycoplasmal lipopeptide. (1st June 2019) - Haodang, Luo; Lianmei, Qin; Ranhui, Li; Liesong, Chen; Jun, He; Yihua, Zeng; Cuiming, Zhu; Yimou, Wu; Xiaoxing, You
Abstract: Exposure to Mycoplasma pneumoniae leads to lung inflammation through a host defense pathway. Increasing evidence has indicated that the mycoplasma-derived membrane lipoprotein, or its analogue macrophage-activating lipopeptide-2 (MALP-2), excretes LPS as an immune system-stimulating substance and plays a crucial role in pathological injury during M. pneumoniae infection. It has been established that Sulforaphane confers anti-inflammatory properties. However, the underlying mechanism responsible for the inhibitory actions of Sulforaphane in the context of mycoplasmal pneumoniae are poorly understood. Here, we report that Sulforaphane is an inducer of heme oxygenase (HO)-1, a cytoprotective enzyme that catalyzes the degradation of heme through signaling pathways in human monocytes. Sulforaphane stimulated NF-E2-related factor 2 (Nrf2) translocation from the cytosol to the nucleus, and small interfering RNA-mediated knock-down of Nrf2 significantly inhibited Sulforaphane-induced HO-1 expression. Additionally, PI3K/Akt and ROS were also involved in Sulforaphane-induced Nrf2 activation and HO-1 expression, as revealed by the pharmacological inhibitors LY294002 and NAC. Moreover, Sulforaphane treatment inhibited MALP-2-induced pro-inflammatory cytokine secretion and pulmonary inflammation in mice, as well as MALP-2-triggered NF-κB activation. Furthermore, SnPP, a selective inhibitor of HO-1, reversed the inhibitory actions of Sulforaphane, while a carbon monoxide-releasing molecule, CORM-2, caused a significant decrease in MALP-2-induced cytokine secretion. Collectively, these results suggest that Sulforaphane functions as a suppressor of the MALP-2-induced inflammatory response, not only by inhibiting the expression of cytokines and the induction of HO-1 but also by diminishing NF-κB activation in cultured monocytes and the lungs of mice. Highlights: Sulforaphane induced THP-1 cells exprssion of HO-1 through PI3K/Akt, ROS and Nrf2. Sulforaphane could attenuate Mycoplasmal lipopeptide-induced inflammation. The inhibitory effect of Sulforaphane was mediated by HO-1 and NF-κB.